2011
DOI: 10.4149/gpb_2011_03_263
|View full text |Cite
|
Sign up to set email alerts
|

Modulations of behavioral consequences of minor cortical ischemic lesion by application of free radicals scavengers

Abstract: Abstract. Functional and morphological consequences of ischemic lesions are partially related to the production of reactive oxygen species (ROS). The aim of the study was to create a unilateral photothrombic lesion with minimal morphological changes and minor sensorimotor and cognitive deficits and also to test whether the application of ROS scavengers after the end of induction of ischemia had improved the functional outcome.Adult Wistar male rats were randomly divided into five groups: naive control, sham op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
1
Order By: Relevance
“…An excitotoxic release of glutamate after ischemia is also known to contribute to brain damage through extreme activation of nNOS (neuronal nitric oxide synthase) and subsequent NO • production ( Moro et al 2004). In the hemisphere contralateral to the ischemia hemisphere, the observed increase in NO • could have been caused by a similar increase in ischemia-induced glutamatergic activity (Duchemin et al 2012). We must take into account that the increased local production of NO could be related to its production in neurons and glial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excitotoxic release of glutamate after ischemia is also known to contribute to brain damage through extreme activation of nNOS (neuronal nitric oxide synthase) and subsequent NO • production ( Moro et al 2004). In the hemisphere contralateral to the ischemia hemisphere, the observed increase in NO • could have been caused by a similar increase in ischemia-induced glutamatergic activity (Duchemin et al 2012). We must take into account that the increased local production of NO could be related to its production in neurons and glial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Photo-chemically induced thrombosis (photothrombosis) of cerebral vessels caused by production of singlet oxygen in laser irradiated areas is Vol. 65 a commonly used model of ischemic lesions in the cerebral cortex (Deykun et al 2011, Watson et al 1985, Watson et al 2002. Using this model, a laser beam focused on the area of interest facilitates the formation of diffuse embolization of smaller vessels or even an obstruction of a large vessel.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, emerging studies have indicated that melatonin exert neuroprotective effects in stroke animals ( Table 2 ) ( Li et al, 1997 ; Kilic et al, 1999 ; Ling et al, 1999 ; Borlongan et al, 2000 ; Sinha et al, 2001 ; Gupta et al, 2002 ; Kondoh et al, 2002 ; Pei et al, 2002 ; Pei et al, 2002 ; Sun et al, 2002 ; Pe and Cheung, 2003 ; Pei et al, 2003 ; Andrabi et al, 2004 ; Gupta et al, 2004 ; Lee et al, 2004 ; Pei and Cheung, 2004 ; Torii et al, 2004 ; Zou et al, 2004 ; Kilic E. et al, 2005 ; Kilic U. et al, 2005 ; Lee et al, 2005 ; Chen et al, 2006 ; Chen et al, 2006 ; Zou et al, 2006 ; Lee et al, 2007 ; Koh, 2008a ; Koh, 2008b ; Koh, 2008c ; Koh, 2008d ; Koh, 2008e ; Hung et al, 2008 ; Kilic et al, 2008 ; Matejovska et al, 2008 ; Chen et al, 2009 ; Sung et al, 2009 ; Wang et al, 2009 ; Tai et al, 2010 ; Ahmad et al, 2011 ; Deykun et al, 2011 ; Koh, 2011 ; Nair et al, 2011 ; Tai et al, 2011 ; Koh, 2012a ; Koh, 2012b ; Chern et al, 2012 ; Jang et al, 2012 ; Kilic et al, 2012 ; Kilic et al, 2013 ; Liu and Cheung, 2013 ; Ma et al, 2013 ; Bhattacharya et al, 2014 ; Juan et al, 2014 ; Li et al, 2014 ; Zheng et al, 2014 ; Beker et al, 2015 ; Buendia et al, 2015 ; Paredes et al, 2015 ; Yang et al, 2015 ;…”
Section: Protective Effects Of Melatonin In Experimental I/r Injury M...unclassified